Parenting Feeding Styles and Weight Status Among Pre-School Child: Literature Review - Wiwin Lastyana; Wilya Isnaeni; Amelia Ramdani Hasby; Rohani Rohani (Poltekkes Kemenkes Mataram, 2025)
Background: Children who have nutritional problems today not only disrupt their health but also their opportunities in the future. The factors causing poor nutritional status in children are multifactorial, including parenting feeding style.Research Methods: A systematic research review following PRISMA guidelines was conducted to identify, discuss, and integrate recent research investigating the relationship between parenting styles and child obesity. It first summarizes the evidence regarding the role of food parenting practices in shaping and maintaining children's nutritional and weight status. It then describes empirical evidence on the relation between general parenting and children's weight status.Research Result: Six electronic databases were searched using standardized language to identify quantitative studies describing associations of general parenting styles with children’s weight status aged 3–5 years. Eligible peer-reviewed journal articles published between 2018 and 202 0 were included. Eleven studies met the inclusion criteria. Few studies focused on general feeding. Most studies focused on controlling food parenting practices and general parenting styles. Parental restriction of food was positively associated with child obesity, while pressure to eat and monitoring yielded inconsistent results.Conclusion: Parenting styles are consistently associated with weight status among young children. Research is needed to identify positive parenting behaviors around a child's weight that may be used as targets for health promotion.